The Comprehension of the Sexuality of the Brazilian and Portuguese Elderly, in the Nursing Consultation Context - Saraiva, Renata (2018)
This present study aims to describe, understand and discuss subjectivity and intersubjectivity between nurses and clients in the educational action sexuality of the elderly in the context of the nursing consultation. The relevance was to listen to the elderly and nurses in the mentioned countries, with the intention of promoting reflections and probable changes of sharing, sharing experiences of the existing cultural plurality. It is a qualitative research, founded without theoreticalmethodological reference of the sociological phenomenology of Alfred Schutz. Participated 41 elderlies and 26 nurses. The scenarios were the HESFA- Brazil and the IPG -Portugal, in accordance with the ethical criteria, National Health Council, resolution 466/12. Resulted in concrete categories of lived that revealed the "reasons-why" of the elderly and nurses. Therefore, the absence of intention demonstrates the need to discuss the subject in theory since graduation and, in the practical field, in nursing consultations.